2015
DOI: 10.1016/j.stemcr.2014.10.011
|View full text |Cite|
|
Sign up to set email alerts
|

Early Depletion of Primordial Germ Cells in Zebrafish Promotes Testis Formation

Abstract: SummaryAs complete absence of germ cells leads to sterile males in zebrafish, we explored the relationship between primordial germ cell (PGC) number and sexual development. Our results revealed dimorphic proliferation of PGCs in the early zebrafish larvae, marking the beginning of sexual differentiation. We applied morpholino-based gene knockdown and cell transplantation strategies to demonstrate that a threshold number of PGCs is required for the stability of ovarian fate. Using histology and transcriptomic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(119 citation statements)
references
References 50 publications
5
114
0
Order By: Relevance
“…Furthermore, there is a strong correlation between the number of germ cells an individual has during gonadal development and their eventual sexual fate (X. G. Wang et al, 2007a, 2007b; Tzung et al, 2015). These data suggest that a threshold level of oocytes is required for ovarian fate and therefore female sex-determination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is a strong correlation between the number of germ cells an individual has during gonadal development and their eventual sexual fate (X. G. Wang et al, 2007a, 2007b; Tzung et al, 2015). These data suggest that a threshold level of oocytes is required for ovarian fate and therefore female sex-determination.…”
Section: Discussionmentioning
confidence: 99%
“…In zebrafish, early germ cell numbers (counted prior to histologically apparent sex-differentiation) correlate with sex. Individuals with more germ cells were more likely to develop as females than males (Tzung et al, 2015). However, it is not clear whether this is a causative or consequential effect of sex determination, as the timing of sex determination in zebrafish is not well defined.…”
Section: Introductionmentioning
confidence: 99%
“…ZGLP1 is required for ovary or granulosa cell development in various species (34,35), suggesting that this DEG possibly plays a role in RI, which will expedite incipient SS; other DEGs are listed in Dataset S1.…”
Section: Discussionmentioning
confidence: 99%
“…Gene ontology terms of these differentially expressed genes included biological processes such as reproduction (GO:0000003), sexual reproduction (GO:0019953), the reproductive process (GO:0022414), the reproductive developmental process (GO:0003006), gamete generation (GO:0007276), fertilization (GO:0009566) and the reproductive cellular process (GO:0048610). Twenty-one of these transcripts were also shown to have sex-related roles or differential expression in the gonads in previous studies (Table 4) [8,[30][31][32][33][34]. This finding showed that the assembled transcriptome could be reliably used as a reference for differential expression analyses.…”
Section: Application Of the Asian Seabass Transcriptome For Rna-seq Ementioning
confidence: 54%